Weakness of will and its connection with practical reasons - Keshavarz, Samaneh (2018)
This thesis pursues two main goals. First, it aspires to develop a plausible account of weakness of will that can make sense of our attribution of weakness of will to a range of cases. My proposal to account for weakness of will is that weakness of will arises when the agent withdraws (abandons, revises or acts against) her practical commitment(s) without a good enough normative reason. The idea that a proper analysis of weakness of will involves, among other things, the claims about good enough normative reasons leads us to the second purpose of this thesis. This is to consider what happens when the proposed account of weakness of will is conjoined with a theory of reasons. The motivation for doing so has twofold. First, I take it to be a completion of my proposed account since I believe that a proper understanding of weakness of will needs to make use of the notion of practical reasons. Second, this will be an attempt to bridge the gap between two relatively independent debates, the dispute over “weakness of will” and “practical reasons”; and I take this to be a distinctive contribution of my thesis. To elaborate my proposal further by adding to it a theory of reasons, I will combine the proposed account of weakness of will with Humeanism and Kantianism in turn, and consider the implications of the resulting conjoint view.